Switching from tenofovir to abacavir in HIV-1-infected patients with low bone mineral density: changes in bone turnover markers and circulating sclerostin levels. (13th March 2015) - Negredo, Eugènia; Diez-Pérez, Adolfo; Bonjoch, Anna; Domingo, Pere; Pérez-Álvarez, Núria; Gutierrez, Mar; Mateo, Gracia; Puig, Jordi; Echeverría, Patricia; Escrig, Roser; Clotet, Bonaventura
Abstract: Background: Tenofovir is involved in accelerated bone mineral density (BMD) loss. Methods: We recently published a hip BMD improvement at week 48 [+2.1% (95% CI: −0.6, 4.7) ( P  = 0.043)] in HIV-infected patients with osteopenia/osteoporosis randomized to switch from tenofovir to abacavir ( n  = 26), although without reaching statistical significance compared with those who maintained tenofovir ( n  = 28). Here, we present changes at week 48 in bone markers [C-terminal telopeptide of collagen type 1 (CTX), osteocalcin and procollagen type 1 N propeptide (P1NP)] as well as in circulating levels of three proteins involved in bone regulation [osteoprotegerin, receptor activator for NF-κB ligand (RANKL) and sclerostin, a selective regulator of bone formation through the Wnt pathway] in 44 of these patients. χ 2 or Fisher and Student t -tests were performed according to the distribution of the variables. Results: Bone markers decreased only in the abacavir group [mean (SD) CTX changed from 0.543 (0.495) to 0.301 (0.306) ng/mL; mean (SD) osteocalcin changed from 23.72 (22.20) to 13.95 (12.40) ng/mL; and mean (SD) P1NP changed from 54.68 (54.52) to 28.65 (27.48) ng/mL ( P  < 0.001 in all cases)], reaching statistical significance between the groups at week 48. Osteoprotegerin did not vary, but sclerostin significantly increased in the abacavir group [from 29.53 (27.91) to 35.56 (34.59) pmol/L, P  = 0.002]. No significant differences in osteoprotegerin and sclerostin were detected between the groups at week 48. RANKL values were below the limit of detection in all samples. Conclusions: The switch from tenofovir to abacavir seems to induce a positive effect on bone tissue, since bone turnover markers decreased. In addition, circulating sclerostin levels increased, a change associated with improved bone properties.